Optimal degree of remote work - Justus Bertram; Carsten S. Ruhnke; Jens Robert Schöndube (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2024)
As a new work style remote work has become an increasingly important factor for firms and their employees. Employees potentially benefit from a higher flexibility when working remotely. Firms can make use of this non-financial benefit to increase their attractiveness on the job market and to substitute financial wage payments to the employees. However, working remotely offers chances for the employees to engage in unproductive activities at the cost of productive working time. Hence, firms need to trade off the benefits against the costs in order to decide which degree of remote work is optimal. We use an agency model to examine the optimal degree of remote work and its interaction with the optimal incentive rate. Higher uncertainty in the productive outcome or higher risk aversion of the employee leads to both a lower degree of remote work and a lower incentive rate, while the effect of the employee's productivity on the degree of remote work is ambiguous. If pay-performance sensitivity is sufficiently high, an increase in the employee's productivity leads to a decrease in the degree of remote work, whereas it is the other way around for a low pay-performance sensitivity. In addition, we find that the optimal degree of remote work increases in the employee's preferred degree of remote work. While in the first-best solution the optimal degree of remote work is always higher than the preferred degree, in the second-best solution it can be higher or lower.
Keywords: C02; D82; D83; J21; J22; J24; J33; L23; M51; M52; 330; Remote Work; New Work Style; Agency Theory; Multi-Task Problem